Biotechnological Enhancement of Probiotics through Co-Cultivation with Algae: Future or a Trend? - Lucija Perković; Elvis Djedović; Tamara Vujović; Marija Baković; Tina Paradžik; Rozelindra Čož-Rakovac (Marine Drugs, 2022)
The diversity of algal species is a rich source of many different bioactive metabolites. The compounds extracted from algal biomass have various beneficial effects on health. Recently, co-culture systems between microalgae and bacteria have emerged as an interesting solution that can reduce the high contamination risk associated with axenic cultures and, consequently, increase biomass yield and synthesis of active compounds. Probiotic microorganisms also have numerous positive effects on various aspects of health and represent potent co-culture partners. Most studies consider algae as prebiotics that serve as enhancers of probiotics performance. However, the extreme diversity of algal organisms and their ability to produce a plethora of metabolites are leading to new experimental designs in which these organisms are cultivated together to derive maximum benefit from their synergistic interactions. The future success of these studies depends on the precise experimental design of these complex systems. In the last decade, the development of high-throughput approaches has enabled a deeper understanding of global changes in response to interspecies interactions. Several studies have shown that the addition of algae, along with probiotics, can influence the microbiota, and improve gut health and overall yield in fish, shrimp, and mussels aquaculture. In the future, such findings can be further explored and implemented for use as dietary supplements for humans.